Influência da intensidade luminosa, do jejum pré-colheita e do tempo de estocagem sobre parâmetros bioquímicos no soro e plasma de frangos de corte - Polese, Clauber (2022)
The objective of this work was to evaluate the effect of the light intensity (5 and 20 lux), the fasting time, to which the birds were submitted and the storage time at -20 ºC of serum and plasma samples (sodium fluoride + EDTA K3), on the concentrations of total proteins, albumin, globulin, uric acid, creatinine, calcium, phosphorus and alkaline phosphatase enzyme activity in broilers at 45 days of age. For that, two experiments were carried out. In the first one, 70 male Cobb 500 broilers at 45 days of age were used in a completely randomized design in a 2 x 7 x 3 factorial scheme, submitted to blood samples after 0, 2, 4, 6, 8, 10 and 12 hours of fasting, with serum and plasma analyzes performed at time 0 and after 30 and 60 days of storage at - 20 ºC. There was no effect of fasting times and storage times on serum and plasma concentrations of total proteins, albumin and globulin. When applied regression, creatinine and alkaline phosphatase showed a quadratic effect, with a maximum concentration of 0.208 mg dL-1 with 4 hours and 32 minutes of fasting and alkaline phosphatase with a minimum value of 2933.31 mg dL-1 with 8 hours of fasting. In plasma, total proteins, albumin, and creatinine showed a quadratic effect for fasting time, maximum value of 35.46 g L-1 at 7 hours and 48 minutes for total proteins, 15.36 g L-1 at 10 hours and 48 minutes for albumin, 0.18 mg dL-1 with 7 hours and 46 minutes for creatinine. For the analysis of total proteins, albumin and globulins, both serum and plasma fractions and 12 hours of fasting can be used and the samples can be stored for up to 60 days at -20°C. For uric acid analyses, both serum or plasma fractions and 12 hours of fasting can be used, but analysis immediately after collection is recommended. It is recommended to use serum for analysis of creatinine and alkaline phosphatase activity, with storage for 30 days at -20 ºC. Plasma for analysis of alkaline phosphatase activity can be stored for up to 60 days at -20°C. In the second experiment, 140 male 45-day-old Cobb 500 broilers were used in a completely randomized design in a 2 x 7 x 5 x 3 factorial scheme, separated into two environments of light intensity (5 and 20 lux). Blood samples were collected from 10 birds from each environment and at each fasting period (0, 2, 4, 6, 8, 10 and 12 hours). Serum and plasma samples were stored at -20 ºC for 0, 15, 30, 60 and 120 days, and biochemical analyzes were performed after these periods. There was a linear effect of fasting time on albumin with a decrease of 0.097 g L-1, while alkaline phosphatase increased its serum activity by 38.55 IU L-1 for each hour of fasting. There was also both quadratic and cubic effects for uric acid, total proteins, globulin and creatinine, as well as linear and cubic effects for calcium. For uric acid, a minimum concentration of 2.20 mg dL-1 was obtained after 4 hours and 51 minutes of fasting. Total proteins had maximum serum concentration by the quadratic regression model of 36.18 g L-1 with 04 hours and 30 minutes of fasting, globulin with maximum concentration of 31.03 g L-1 with 06 hours of fasting. Creatinine had a maximum concentration of 0.182 mg dL-1 with 5 hours and 15 minutes of fasting. The linear model for calcium estimated a reduction in its concentration by 0.09 mg dL-1 for each hour of fasting. Regression analysis indicated a linear increase in serum levels of uric acid, total proteins and globulin as storage time increased. By the quadratic regression model, creatinine had a maximum concentration in serum of 0.184 mg dL-1 at 42 days of storage, calcium and phosphorus showed minimum concentration points at 82 days and 119 days of storage, with 6.63 mg dL-1 and 7.17 mg dL-1, respectively. In plasma, there was a quadratic effect for uric acid, calcium and phosphorus with a minimum of 2.08 mg dL-1, 1.77 mg dL-1 and 5.03 mg dL- 1, with 3 hours and 48 minutes, 5 hours and 45 minutes and 30 minutes of fasting, respectively. The linear model indicated a reduction in plasma alkaline phosphatase activity by 24.92 IU L-1 for each hour of fasting. Globulin and alkaline phosphatase showed a concentration increase of 0.0097 g L-1 and 2.76 IU L-1 for each day of storage, in contrast to creatinine, which decreased by 0.00018 mg dL-1. Uric acid and phosphorus showed maximum concentrations of 2.64 mg dL-1 and 5.47 mg dL-1 at 101 and 62 days of storage, respectively. For analysis of total proteins both fractions can be used. Plasma can be stored for up to 120 days, for the serum fraction storage for up to 60 days at -20 ºC is recommended. The quadratic regression models estimated 6 and 7 hours of fasting for serum and plasma, respectively. Both serum and plasma fractions can be used to measure uric acid and creatinine, but analysis is recommended immediately after sample collection. Serum and plasma phosphorus concentrations were not affected by storage time, and samples can be stored for up to 120 days. With the exception of creatinine and plasma calcium, the other variables showed higher concentrations when using 5 lux, both in serum and plasma. It is not recommended to use the anticoagulant ETDA for the measurement of calcium and alkaline phosphatase activity.